Quantitative systems pharmacology model of α‐synuclein pathology in Parkinson's disease‐like mouse for investigation of passive immunotherapy mechanisms - Olga Ivanova; Tatiana Karelina (Wiley, 2024)
Abstract The main pathophysiological hallmark of Parkinson's disease (PD) is the accumulation of aggregated alpha‐synuclein (αSyn). Microglial activation is an early event in PD and may play a key role in pathological αSyn aggregation and transmission, as well as in clearance of αSyn and immunotherapy efficacy. Our aim was to investigate how different proposed mechanisms of anti‐αSyn immunotherapy may contribute to pathology reduction in various PD‐like mouse models. Our mechanistic model of PD pathology in mouse includes αSyn production, aggregation, degradation and distribution in neurons, secretion into interstitial fluid, internalization, and subsequent clearance by neurons and microglia. It describes the influence of neuroinflammation on PD pathogenesis and dopaminergic neurodegeneration. Multiple data from mouse PD models were used for calibration and validation. Simulations of anti‐αSyn passive immunotherapy adequately reproduce preclinical data and suggest that (1) immunotherapy is efficient in the reduction of aggregated αSyn in various models of PD‐like pathology; (2) prevention of aSyn spread only does not reduce the pathology; (3) a decrease in microglial inflammatory activation and aSyn aggregation may be alternative therapy approaches in PD‐like pathology.